Revisiting an Ongoing Debate: What Role Do Surface Groups Play in Silicon Nanocrystal Photoluminescence? - Sinelnikov, Regina; Dasog, Mita; Beamish, John; Meldrum, Al; Veinot, Jonathan G. C (ACS photonics, 2017)
The origin of photoluminescence (PL) in silicon nanocrystals (SiNCs) remains a subject of considerable debate. Size-dependent PL that supports the quantum confinement model has been proposed by several researchers. On the other hand, SiNC PL arising from surface states that are independent of nanocrystal size has also been shown. This work addresses the origin of surface-functionalized SiNC PL as relating to surface states and the NC size. SiNCs of different sizes (3 and 5 nm diameters) were prepared with three distinct surface chemistries. Steady-state and time-resolved PL measurements were performed at temperatures ranging from 37 to 377 K. Temperature-dependent luminescence consistent with core emission was observed for alkyl-terminated SiNCs, while alkylamine-functionalized SiNCs displayed minimal temperature-dependent luminescence, consistent with a charge-transfer mechanism. Lightly oxidized alkyl SiNCs had similar emission profiles to alkyl SiNCs; however, they showed longer luminescence lifetimes and their luminescence spectrum was shifted to shorter wavelengths than their nonoxidized counterparts. A general mechanism is proposed to explain all three phenomena, suggesting that surface groups play a crucial role in SiNC optical response.